Development and Use of a Traditional Mexican Diet Score in Relation to Systemic Inflammation and Insulin Resistance among Women of Mexican Descent. Issue 12 (21st October 2015) - Santiago-Torres, Margarita; Tinker, Lesley F; Allison, Matthew A; Breymeyer, Kara L; Garcia, Lorena; Kroenke, Candyce H; Lampe, Johanna W; Shikany, James M; Van Horn, Linda; Neuhouser, Marian L
Abstract: Background: Women of Mexican descent are disproportionally affected by obesity, systemic inflammation, and insulin resistance (IR). Available approaches used to give scores to dietary patterns relative to dietary guidelines may not effectively capture traditional diets of Mexicans, who comprise the largest immigrant group in the United States. Objectives: We characterized an a priori traditional Mexican diet (MexD) score high in corn tortillas, beans, soups, Mexican mixed dishes (e.g., tamales), fruits, vegetables, full-fat milk, and Mexican cheeses and low in refined grains and added sugars and evaluated the association of the MexD score with systemic inflammation and IR in 493 postmenopausal participants in the Women's Health Initiative (WHI) who are of Mexican ethnic descent. Methods: The MexD score was developed from the baseline (1993–1998) WHI food frequency questionnaire, which included Hispanic foods and was available in Spanish. Body mass index (BMI) was computed from baseline measured weight and height, and ethnicity was self-reported. Outcome variables were high sensitivity C-reactive protein (hsCRP), glucose, insulin, homeostasis model assessment of insulin resistance (HOMA-IR), and triglyceride concentrations measured at follow-up (2012–2013). Multivariable linear and logistic regression models were used to test the associations of the MexD score with systemic inflammation and IR. Results: The mean ± SD MexD score was 5.8 ± 2.1 (12 maximum points) and was positively associated with intakes of carbohydrates, vegetable protein, and dietary fiber and inversely associated with intakes of added sugars and total fat ( P < 0.01). Women with high compared with low MexD scores, consistent with a more-traditional Mexican diet, had 23% and 15% lower serum hsCRP ( P < 0.05) and insulin concentrations, respectively ( P < 0.05). Baseline BMI modified these associations such that lower MexD scores were associated with higher insulin and HOMA-IR in overweight/obese women ( P -interaction <0.05). Conclusion: These findings suggest that greater adherence to a traditional Mexican diet could help reduce the future risk of systemic inflammation and IR in women of Mexican descent.